(untitled) (SAARC Journal of Agriculture, 2024)
A field experiment was carried out at Sher-e-Bangla Agricultural University in Dhaka from November 2021 to June 2022 using a Randomized Complete Block Design (RCBD) with three replications to assess the significance of variance, heritability, genetic advance, correlation, path coefficient and genetic diversity for different yield contributing parameters in twenty brinjal genotypes. High heritability associated with high genetic advance and high genetic advance in percentage of mean was found in plant height, individual fruit weight and percent of brinjal shoot and fruit borer infestation, which indicated selection based on phenotype would be effective. Assessments of character association indicated that fruit yield plant-1 had highest significant positive correlation with days of last harvesting (rg= 0.495, rp= 0.454), number of secondary branches plant-1 (rg=0.356, rp=0.315), leaf blade length (rg = 0.714, rp = 0.462), leaf blade width (rg = 0.674, rp = 0.498) and number of fruits plant-1 (rg= 0.798, rp= 0.787) in both genotypic and phenotypic level. Path analysis revealed that the number of flowers plant-1 (1.421) had the maximum positive and direct effect on yield plant-1. According to PCA, D2 and Cluster analysis, twenty brinjal genotypes were grouped into five different clusters- I, II, III, IV and V with three, three, four, six and four genotypes respectively. Considering magnitude of cluster mean performance and genetic parameters genotypes G10 (Choto Katali), G20 (BARI Bt Begun 2), G11 (BARI Hybrid Begun 2), G8 (BARI Begun 6), G5 (BARI Hybrid Begun 4), G18 (Local Black Long) might be used in future breeding program. SAARC J. Agric., 22(1): 59-71 (2024)